Ramadan Fasting and Risk of Coronavirus Disease 2019 (Covid-19) in Healthy People: A Review - Balsam Qubais Saeed; Kubais Saeed Fahady; Ahmed Omar Adrees (Indian Journal of Forensic Medicine & Toxicology, 2021)
Fasting the month of Ramadan is one of five obligatory pillars of the Islamic creed, observed strictly byhundreds of millions of Muslims every year. The fasting process includes absolute abstinence from eatingand drinking for an average of around 15 hours daily for one month. As the coronavirus disease 2019(COVID-19) pandemic has been ongoing during the month of fasting, there are public concerns that fastingmay increase the susceptibility for infection of COVID-19. According to Islamic jurisdiction, if adequatescientific evidence of harm on health is available, fasting is discouraged and should not be practiced.Such concern is not only relevant to the Muslim population but is becoming increasingly relevant to otherpopulations due to the practice of intermittent fasting which is a popular current health trend worldwide.There is no direct evidence of any disadvantage effect of Ramadan fasting during the COVID-19 pandemicon healthy people, for this purpose, we performed a systematic review of 37 articles published between2005 and April 2020 which investigated the effect of fasting on markers of the respiratory system functionand immune response. Our main findings from this analysis show that there is no evidence that fasting themonth of Ramadan have a negative impact on the respiratory function and the immune system of healthyindividuals.